PEPA: Pedagogías del Paro. Estrategias didácticas para el abordaje de la movilización social en la educación básica primaria - Caro Parrado, Jonathan; Pulido Patiño, Kelly Yojana; Yáñez Godoy, Luis Enrique (Educación y Ciudad, 2022)
This article addresses the experience of political participation of the IED Juana Escobar school in the social mobilization generated by the social outbreak of Colombia (2019-2021) based on the PEPA strategy: Pedagogies of the social strike. This was implemented specifically in primary school, from the perspective of three teachers who actively built pedagogical processes in their educational practice inside and outside the classroom, which allow the resignification of their teaching role by achieving curricular articulation, active construction of citizenship, political partition, reflectivity and critical sense with their students and educational community.